AI-based Personalization of Social Media Thumbnails Using the Stacked ID Embedding Method - Meivi Kartikasari; Hashfi Andira Putra; Mukhlis Amien (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
Social media content creators find it hard to make thumbnails shine on Instagram, YouTube, and TikTok, where graphic design skills happen to be a significant bottleneck. To address this issue, scientists developed a text-based image generation model, PotionPix, that allows users to generate thumbnails on the fly based on text prompts and relevant images via a